Block compost for acid mine drainage remediation and as a growing medium for Melaleuca cajuputi seedlings - Daniswati, Nisa; Mansur, Irdika; Herliyana, Elis Nina (Journal of Degraded and Mining Lands Management, 2026)
Environmental problems arising from mining include the formation of acid mine drainage (AMD), which contains high levels of heavy metals and has a low pH, requiring remediation. Block compost made from goat manure and mushroom baglog waste has the potential to remediate AMD and serve as a planting medium. The objectives of this study were to analyze the effect of block compost on AMD remediation and to assess its effect as a planting medium on the growth of Melaleuca cajuputi. This study used a completely randomized design with six block compost composition treatments: without block compost (P0), mushroom baglog waste 70% + cement 30% (P1), goat manure 70% + cement 30% (P2), goat manure 35% + mushroom baglog waste 35% + cement 30% (P3), goat manure 25% + mushroom baglog waste 45% + cement 30% (P4), goat manure 45% + mushroom baglog waste 25% + cement 30% (P5). The results showed that the treatment of block compost with various compositions (P1, P2, P3, P4, P5) was effective in increasing the pH of AMD from 3 to 5.1-6.4 and reducing the concentration of Cd, Cu, Pb, and Zn metals by 45.74-82.70% within 5 days. The application of block compost with various compositions also had a significant effect on the height growth of Melaleuca cajuputi. The P3 treatment significantly increased the height of the seedlings to 34.00 cm within 8 weeks.